Formation of super-assembled TiOx/Zn/N-doped carbon inverse opal towards dendrite-free Zn anodes - Sun, Peng Xiao (2022)
Uncontrolled growth of Zn dendrites and side reactions are the major restrictions for the commercialization of Zn metal anodes. Herein, we develop a TiOx /Zn/N-doped carbon inverse opal (denoted as TZNC IO) host to regulate the Zn deposition. Amorphous TiOx and Zn/N-doped carbon can serve as the zincophilic nucleation sites to prevent the parasitic reactions. More importantly, the highly ordered IO host homogenizes the local current density and electric field to stabilize Zn deposition. Furthermore, the three-dimensional open networks could regulate Zn ion flux to enable stable cycling performance at large current densities. Owing to the abundant zincophilic sites and the open structure, granular Zn deposits could be realized. As expected, the TZNC IO host guarantees the steady Zn plating/stripping with a long-term stability over 450 h at the current density of 1 mA cm-2 . As a proof-of-concept demonstration, a TZNC@Zn||V2 O5 full cell shows long lifespan over 2000 cycles at 5.0 A g-1 .